НАСЛЕДСТВЕННЫЙ АНГИООТЁК В БЕЛАРУСИ: КЛИНИЧЕСКАЯ ХАРАКТЕРИСТИКА И ИСПОЛЬЗУЕМАЯ ТЕРАПИЯ - Гурьянова, Ирина Евгеньевна; Жаранкова, Юлия Сергееввна; Овсяник, Ирина Васильевна; Алешкевич, Светлана Николаевна; Белевцев, Михаил Владимирович (FORCIPE, 2022)